2022
DOI: 10.1002/anie.202117700
|View full text |Cite
|
Sign up to set email alerts
|

Thionolactone as a Resin Additive to Prepare (Bio)degradable 3D Objects via VAT Photopolymerization**

Abstract: Three‐dimensional (3D) printing and especially VAT photopolymerization leads to cross‐linked materials with high thermal, chemical, and mechanical stability. Nevertheless, these properties are incompatible with requirements of degradability and re/upcyclability. We show here that thionolactone and in particular dibenzo[c,e]‐oxepane‐5‐thione (DOT) can be used as an additive (2 wt %) to acrylate‐based resins to introduce weak bonds into the network via a radical ring‐opening polymerization process. The low amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…Recently, Thoniyot et al reported that the insertion of an ester unit in poly­(acrylic acid) via the use of MDO led to an interesting degree of biodegradability (27.50% in 28 days) in standard conditions (OECD 301F) compared to no biodegradation for the reference poly­(acrylic acid). Our group also reported preliminary results of biodegradation for degradable 3D objects obtained using DOT as an additive using homemade compost . In this study, PS3 and Copo3 were finally tested for bacterial degradation.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Recently, Thoniyot et al reported that the insertion of an ester unit in poly­(acrylic acid) via the use of MDO led to an interesting degree of biodegradability (27.50% in 28 days) in standard conditions (OECD 301F) compared to no biodegradation for the reference poly­(acrylic acid). Our group also reported preliminary results of biodegradation for degradable 3D objects obtained using DOT as an additive using homemade compost . In this study, PS3 and Copo3 were finally tested for bacterial degradation.…”
Section: Resultsmentioning
confidence: 85%
“…Our group also reported preliminary results of biodegradation for degradable 3D objects obtained using DOT as an additive using homemade compost. 43 In this study, PS3 and Copo3 were finally tested for bacterial degradation. As said previously, the biodegradation of polystyrene has been investigated using a wide range of fungi, microbes, and invertebrates.…”
Section: Thermal and Mechanical Properties Of P(s-co-dot)mentioning
confidence: 99%
“…41 DOT is compatible with both FRP and RDRP and affords degradation via cleavage of the backbone thioester by, for example, primary amines, strong bases, or thiols. Very recently, Guillaneuf et al used DOT in crosslinked systems and reported that a 3D-printed poly(pentaerythritol triacrylate) 42 and a poly(styrene-co-divinylbenzene) 41 both underwent degradation with 2 wt % and 5 mol % of DOT, respectively. However, there has been neither a systematic study to optimize the ratio of DOT to crosslinker to achieve degradability nor a confirmation of the reverse gel-point model for radically made networks.…”
Section: ■ Introductionmentioning
confidence: 99%
“…67 TARO monomers have also found a use in producing degradable cross-linked materials through uncontrolled radical polymerization. 68,71 Incorporation of only 4 mol% of DOT into acrylate-based networks led to the ability to completely degrade the insoluble materials. The low incorporation allowed for the retention of the physical properties of the network, compared to non-degradable controls, and 3D-print some of the structures.…”
Section: Reviewmentioning
confidence: 99%
“…-2-Methoxyethoxyacrylamide 67 N,N-Dimethylacrylamide 63,66,70 N,N-Diethylacrylamide 66 N-3-(N-4-Sulfobutyl-N,N-dimethylammonium) propylacrylamide 66 Acrylonitrile 63,66Pentaerythritol triacrylate71 Styrene 69,72 N-Methylmaleimide65 Alternating copolymerization between the thiocarbonyl species and the vinyl comomomer N-Phenylmaleimide 65 N-Pentafluorophenylmaleimide65 …”
mentioning
confidence: 99%